2009
DOI: 10.1016/j.jcrc.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The intensive care unit family meeting: Making it happen

Abstract: The intensive care unit (ICU) family meeting is an important forum for discussion about the patient’s condition, prognosis, and care preferences; for listening to the family’s concerns; and for decision making about appropriate goals of treatment. For patients, families, clinicians, and health care systems, the benefits of early and effective communication through these meetings have been clearly established. Yet, evidence suggests that family meetings still fail to occur in a timely way for most patients in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 43 publications
1
64
0
3
Order By: Relevance
“…One strategy recommended facilitating the initiation of family conferences by using clinical situations as "automatic triggers" for family conferences. 21 We incorporated this strategy into our supportive care algorithm through the use of clinical triggers ( Figure 1A-1C). These triggers were identified by the team as clinical conditions commonly associated with a high risk of patient death in our SICU.…”
Section: Planning the Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…One strategy recommended facilitating the initiation of family conferences by using clinical situations as "automatic triggers" for family conferences. 21 We incorporated this strategy into our supportive care algorithm through the use of clinical triggers ( Figure 1A-1C). These triggers were identified by the team as clinical conditions commonly associated with a high risk of patient death in our SICU.…”
Section: Planning the Interventionmentioning
confidence: 99%
“…12 Formal scheduled family meetings involving multiple disciplines are an effective approach to talking with patients' families and encouraging dialogue about care. [19][20][21] Interdisciplinary family conference should occur within 72 hours of admission; documentation should include what was discussed. 13,22,23 ICU family conferences within 72 hours have been associated with reduced number of days in the ICU for patients who die and with higher ratings of the quality of dying among family members.…”
Section: Planning the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the best timing for an initial family conference has not been established, nor has the optimal frequency been determined. Gay 7 and colleagues reported multiple barriers to conducting family conferences in the ICU, such as competing time demands, lack of appropriate space, cultural and language difficulties, and inadequate clinician training in communication skills. Strategies to overcome these and other barriers are needed.…”
Section: Beyond Family Conferencesmentioning
confidence: 99%
“…Gay and colleagues state, "Almost universally, it is the bedside nurse who develops the closest relationship with both the ICU patient and the family." 7 In their qualitative study of nurse communications in the ICU, Slatore and colleagues 9 identified a theme of a key role for the nurse in serving as a translator or intermediary between physicians and patients/families. However, they further identified that nurses made a distinction between topics that they were and were not willing to discuss with patients and families.…”
Section: " "mentioning
confidence: 99%